The buckling of three-phase orthotropic composite plates used in composite shipbuilding - Pham, Van Thu (H. : ĐHQGHN, 2019)
This paper presents the investigation on the buckling of three-phase orthotropic composite plates used in shipbuilding subjected to mechanical loads by analytical approach. The basic equations are established based on the Classical Plate Theory. The analytical method is used to obtain the expressions of critical loads of the three-phase composite plate. The results in the article are compared to the results obtained by other authors to validate the reliability of the present method. The approach in this direction is for. The effects of fiber and particle volume fraction, material and geometrical parameters on the critical load of three-phase composite plates are discussed in detail.